Issues of development of certain areas with the help of taxes and their improvement (Eurasian Research Bulletin, 2023)
This annotation is for the topic of the development and improvement of certain regions of Uzbekistan through the use of taxes. The study will focus on the challenges and opportunities associated with using tax policies to stimulate economic growth and development in specific regions of the country. The literature review will explore international best practices in regional tax policies, as well as the specific context and challenges facing Uzbekistan. The study aims to provide recommendations and solutions for improving tax policies and their implementation to support the growth and development of underdeveloped regions in Uzbekistan. The findings of this study will be useful for policymakers, researchers, and anyone interested in the economic development of Uzbekistan..